(untitled) (International journal of artificial intelligence, 2025)
This article is devoted to familiarizing students of higher educational institutions with the concept of physical qualities through the use of innovative technologies. It discusses modern methods of teaching movements, their classification, and significance. The importance of organizing the educational process and its effectiveness is revealed in the context of how physical qualities affect the human body. Lesson design includes certain requirements, construction principles, algorithms, and features that play a key role in organizing the participants’ activities and achieving educational outcomes. The article also focuses on the role of pedagogical technologies in teaching the subject “Theory and Methodology of Physical Education.”